2021
DOI: 10.3390/foods10020230
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Parasitic Activity of Cherry Tomato Peel Powders

Abstract: Trichomoniasis in humans, caused by the protozoal parasite Trichomonas vaginalis, is the most common non-viral sexually transmitted disease, while Tritrichomonas foetus causes trichomonosis, an infection of the gastrointestinal tract and diarrhea in farm animals and domesticated cats. As part of an effort to determine the inhibitory effects of plant-based extracts and pure compounds, seven commercially available cherry tomato varieties were hand-peeled, freeze-dried, and pounded into powders. The anti-trichomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Lycopene is a phytonutrient playing an important role in human health. Indeed, it has long been known for its several biological activities such as antioxidant [ 10 ], anti-inflammation [ 11 ], hypoglycemic [ 12 , 13 ], photoprotection [ 14 ], anti-angiogenesis [ 15 ], anti-parasitic [ 16 , 17 , 18 , 19 ], antiviral [ 20 ] and others. Several studies have also indicated the effect of dietary lycopene in reducing the risk of chronic diseases such as coronary heart disease [ 21 ], being also useful in reducing the oxidative stress in human immunodeficiency virus (HIV)-infected patients under antiretroviral therapy that have less total antioxidant capacity [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lycopene is a phytonutrient playing an important role in human health. Indeed, it has long been known for its several biological activities such as antioxidant [ 10 ], anti-inflammation [ 11 ], hypoglycemic [ 12 , 13 ], photoprotection [ 14 ], anti-angiogenesis [ 15 ], anti-parasitic [ 16 , 17 , 18 , 19 ], antiviral [ 20 ] and others. Several studies have also indicated the effect of dietary lycopene in reducing the risk of chronic diseases such as coronary heart disease [ 21 ], being also useful in reducing the oxidative stress in human immunodeficiency virus (HIV)-infected patients under antiretroviral therapy that have less total antioxidant capacity [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…We reported that tomatine inhibited the growth of Trichomonas vaginalis strain G3, Tritrichomonas foetus strain Dl, and Tritrichomonas foetus-like strain Cl that cause sexually transmitted diseases in humans and farm and domesticated animals (cows, pigs, cats, and dogs); extracts from tomato peels also inhibited the pathogenic microorganism Salmonella at higher concentrations [24][25][26][27]. The report that tomatine behaves as an adjuvant in a malaria vaccine offers hope for an improved anti-malaria vaccine [33].…”
Section: Antibiotic Effectsmentioning
confidence: 89%
“…Tomatine has also been reported to exhibit several beneficial health-promoting properties. These include antibiotic activities against pathogenic viruses [16], induction of decreased plasma low-density lipoprotein (LDL) cholesterol and triglyceride levels in hamsters fed a high saturated fat, high-cholesterol diet [17,18], inhibition of cancer cells in vitro [14,19,20], the growth of multi-organ cancers in rainbow trout [21], the growth and metastasis of transplanted tumors in mice [22], reviewed in Friedman [23], as well as inactivation of parasitic protozoa (trichomonads) that cause the sexually transmitted diseases trichomoniasis in humans, cattle, and cats [24][25][26], reviewed in [27]. Here, we mention highlights on the formation of tomatine in growing tomato plants and antibiotic, cardiopro-tective, anticancer, and other health benefits of tomatine and tomatidine [28] to emphasize their potential value as health-promoting functional foods to motivate further research.…”
Section: Discussionmentioning
confidence: 99%
“…Spooner, G.J. Anderson and R.K. Jansen presented more than 50% activity against T. vaginalis [97]. Eicosapentaenoic acid (EPA), also known as omega-3 polyunsaturated fatty acid, was approximately 90% effective at 24 h (with concentrations of 190 ”M and 380 ”M) against MTZ-sensitive and -resistant T. vaginalis isolates, while 100 ”M abolished parasite growth at 48 h [75].…”
Section: Articles: Natural Productsmentioning
confidence: 99%